2011
DOI: 10.4319/lo.2011.56.2.0599
|View full text |Cite
|
Sign up to set email alerts
|

Temperature and nutrient stoichiometry interactively modulate organic matter cycling in a pelagic algal–bacterial community

Abstract: A microcosm experiment was conducted to investigate the interactive effects of rising sea-surface temperature and altered nutrient stoichiometry on the biogeochemical cycling of organic matter in a pelagic algal-bacterial assemblage. Natural seawater, containing a mixed bacterial community, was inoculated with an axenic culture of the bloom-forming diatom species Skeletonema costatum. A factorial combination of three temperatures, simulating weak to strong warming as projected for the end of the 21st century, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 49 publications
2
17
0
Order By: Relevance
“…Model simulations reveal that whilst near-cell CO 2 and pH conditions are close to those of the bulk water for cells < 5 µm in diameter, they diverge as cell diameters increase (Flynn et al, 2012). This is due to the size-dependent thickness of the diffusive boundary layer, which determines the diffusional transport across the boundary layer and to the cell surface (Wolf-Gladrow and Riebesell, 1997;Flynn et al, 2012). It is suggested that larger cells may be more able to cope with f CO 2 variability as their carbon acquisition is more geared towards handling low CO 2 concentrations in their diffusive boundary layer, e.g.…”
Section: Phytoplankton Dynamicsmentioning
confidence: 99%
See 2 more Smart Citations
“…Model simulations reveal that whilst near-cell CO 2 and pH conditions are close to those of the bulk water for cells < 5 µm in diameter, they diverge as cell diameters increase (Flynn et al, 2012). This is due to the size-dependent thickness of the diffusive boundary layer, which determines the diffusional transport across the boundary layer and to the cell surface (Wolf-Gladrow and Riebesell, 1997;Flynn et al, 2012). It is suggested that larger cells may be more able to cope with f CO 2 variability as their carbon acquisition is more geared towards handling low CO 2 concentrations in their diffusive boundary layer, e.g.…”
Section: Phytoplankton Dynamicsmentioning
confidence: 99%
“…Specifically, a negative relationship between the abundances of HNA prokaryotes and f CO 2 was detected and corresponded to reduced bacterial production and respiration at higher f CO 2 (Hornick et al, 2017;Spilling et al, 2016). Although CO 2 enrichment may not directly affect bacterial growth, a co-occurring global rise in temperature can increase enzyme activities, affecting bacterial production and respiration rates (Piontek et al, 2009;Wohlers et al, 2009;Wohlers-Zöllner et al, 2011). The enhanced bacterial remineralization of organic matter may stimulate autotrophic production by the small-sized phytoplankton Riebesell and Tortell, 2011;Engel et al, 2013), intensifying the selection of small cell sizes.…”
Section: Microbial Loopmentioning
confidence: 99%
See 1 more Smart Citation
“…This decrease in the average ratio of POC to POP may, in fact, rather suggest a temperature-induced shift in the turnover dynamics of organic phosphorus compounds. Thus, results from an AQUASHIFT-related microcosm experiment have shown that experimental warming can substantially stimulate phosphorus cycling through the activity of the organic phosphorus-cleaving enzyme alkaline phosphatase (APA; Wohlers-Zöllner et al 2011), hence enabling a faster replenishment of the POP pool at elevated temperature and reducing the C:P ratio of POM.…”
Section: Organic Matter Elemental Compositionmentioning
confidence: 99%
“…Several mesocosm simulation experiments have examined the potential impacts of rising temperatures alone (Sommer & Lengfellner 2008, Lassen et al 2010, Taucher et al 2012, or in combination with perturbations of pCO 2 (Kim et al 2011), light (Lewandowska & Sommer 2010), nutrients (Wohlers-Zöllner et al 2011) or grazing (Sommer & Lewandowska 2011), on phytoplankton blooms. All of these studies observed an early onset and peak of the spring phytoplankton blooms, which has also been observed in situ (Edwards & Richardson 2004).…”
Section: Temperaturementioning
confidence: 99%